Brief screening measures of mental health for war-related dysfunctional anxiety and negative persistent thinking. (September 2022) - Surzykiewicz, Janusz; Skalski, Sebastian Binyamin; Niesiobędzka, Małgorzata; Gladysh, Olga; Konaszewski, Karol
Abstract: As per previous research, war causes exposure to trauma not only among its participants and refugees, but also broader groups that are influenced by mass media coverage of the war. In addition, according to other reports, dysfunctional anxiety and negative persistent thinking may be clear indicators of mental health in the face of crisis. The purpose of this study was to construct and initially evaluate the psychometric properties of the War Anxiety Scale (WAS) and the War Persistent Thinking Scale (WPTS). The study included 553 Poles between the ages of 18 and 81 (57% of whom were women), and 216 Ukrainian war refugees aged 18–61 (79% of whom were women) who came to Poland. Both scales showed a single-factor structure with strong internal consistency ( α ∈ <0.83;0.93>). WAS and WPTS scores positively correlated with measures of symptoms for posttraumatic stress disorder, depressiveness, and nuclear concern, and negatively correlated with measures of mental resilience and nuclear support. The data obtained indicate that WAS and WPTS are effective and valid tools in clinical research and practice. Highlights: War causes exposure to trauma among its participants and wider contingents. This study evaluates the psychometric properties of the War Anxiety Scale (WAS). Our analysis also considers the War Persistent Thinking Scale (WPTS). WAS and WPTS are effective and valid tools in clinical research and practice.